2020
DOI: 10.1002/ece3.6013
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Squamata (Reptilia) assemblages in Mediterranean archipelagos

Abstract: Mediterranean islands have complex reptile assemblages, but little is known about the factors that determine their organization. In this study, the structure of assemblages of Squamata was evaluated based on their species richness and two measures of phylogenetic diversity (variability and clustering). I evaluated the composition of the assemblages comparing distinct biogeographic subregions within the Mediterranean: Adriatic, Aegean, Balearic, Corsica–Sardinia, Crete, Gulf of Gabés, Ionian Sea, Ligurian Sea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…This finding indicated that no squamate lineages in the Mediterranean basin had greater dispersal capacities than others. It was also feasible that more intense interspecific competition between phylogenetic relatives in small islands (Escoriza, 2020) could counteract the effects of traits that might possibly enhance transmarine dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that no squamate lineages in the Mediterranean basin had greater dispersal capacities than others. It was also feasible that more intense interspecific competition between phylogenetic relatives in small islands (Escoriza, 2020) could counteract the effects of traits that might possibly enhance transmarine dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of at least one species, P. siculus , expansion has been correlated with the rapid decline of island endemic species, but adverse effects have also been postulated for the other species (D'Amico et al., 2018; Mayol‐Serra, 1977). Although islets are colonized by species of alien reptiles that are quite diverse phylogenetically (Escoriza, 2020b), those evolutionarily close to endemics, as using similar resources, are frequently associated with the collapse of native populations (Nikolic et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although islets are colonized by species of alien reptiles that are quite diverse phylogenetically (Escoriza, 2020b), those evolutionarily close to endemics, as using similar resources, are frequently associated with the collapse of native populations (Nikolic et al, 2019).…”
Section: Discussionmentioning
confidence: 99%